How Adolescents’ Family Socioeconomic Status Affects their Career Preparation: The Mediating Effect of Social and Emotional Skills - Cui, Haili (Best Evidence in Chinese Education, 2025)
Drawing on data of 15-year-old Chinese students from the second round of the OECD Survey on Social and Emotional Skills in 2023, this study examines the relationship between family socioeconomic status and career preparation (including exploring the future, experiencing the future, and thinking about the future) in teenagers, as well as the mediating effect of social and emotional skills of the individual on this relationship. The results reveal that the adolescent’s family socioeconomic status not only directly influences their career preparation but also exerts an indirect effect via their social and emotional skills, particularly those in the domains of open-mindedness, task performance, and collaboration.